An innovative method of electro-cauterization to control bleeding - Echchaoui, Abdelmoughit; Amellal, Mina; Jaiteh, Lamin; Boulaadas, Malik (International Surgery Journal, 2017)
The authors describe a simple and innovative method of managing bleeding by monopolar electrocautery in some critical circumstances such as: the lack of bipolar electrocauter, and the surgeon alone without his assistant, or with one who is inexperienced in surgery.